2016
DOI: 10.3892/or.2016.4937
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein screening in colorectal cancer based on differentially expressed Tn antigen

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide, and the identification of new biomarkers for CRC is valuable for its diagnosis and treatment. We aimed to screen differentially expressed glycoproteins (especially O-glycoproteins) and to identify diagnostic or therapeutic candidates for colorectal cancer (CRC) based on different Tn antigen expression levels. Fresh cancer tissues and adjacent healthy tissues were obtained from CRC patients and classified into three groups based on their Tn an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…The heterogeneity of glycosylation sites or changes in glycan structures in body fluids were shown to be correlated with the development and progression of certain cancer states [ 17 , 18 ]. Further, alteration of glycoprotein levels was reported in CRC [ 19 ], breast cancer [ 20 ], and prostate cancer [ 21 ]. Therefore, glycoproteins can be considered an ideal source for the early detection of cancers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of glycosylation sites or changes in glycan structures in body fluids were shown to be correlated with the development and progression of certain cancer states [ 17 , 18 ]. Further, alteration of glycoprotein levels was reported in CRC [ 19 ], breast cancer [ 20 ], and prostate cancer [ 21 ]. Therefore, glycoproteins can be considered an ideal source for the early detection of cancers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Tn antigen is detected in almost 90% of human colon cancer whereas it is rarely detected in normal tissue . Tn antigen expression is correlated with tumour invasion and poor prognosis in CRC patients, and it is proposed as a potential target for immunotherapy . Nevertheless, it remains elusive whether Tn antigen may play a causative role in colorectal cancer development and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, tomoelastography was sensitive to lymphvascular invasion which was not detectable by CVF. This disparity in sensitivity of stiffness and CVF might be due to 1) the contribution of other ECM components than collagen such as fibronectin, proteoglycans, or glycosaminoglycans to tumor stiffness (47,48), or 2), in vivo factors such as blood perfusion and vascular resistance (49) to which tomoelastography is sensitive (17). Tumor angiogenesis and the migration status of neoplastic cells into the vasculature or the lymphatic system probably better reflects lymphvascular invasion than the amount of collagen in the ECM.…”
Section: Discussionmentioning
confidence: 99%